IMPLEMENTATION OF SUPERVISION COACHING BY SCHOOL PRINCIPALS IN IMPROVING THE COMPETENCE AND MOTIVATION OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE BAMBEL DISTRICT OF SOUTHEAST ACEH REGENCY - Zaini Hasan (CV Naskah Aceh, 2025)
This study aims to analyze the implementation of coaching supervision by school principals in improving teachers' competencies and motivation at SD Negeri Kecamatan Bambel, Aceh Tenggara Regency. Coaching supervision, which focuses on empowering teachers through collaborative guidance based on professional needs, is carried out through the stages of planning, implementation, evaluation, and follow-up. This study employs a qualitative method with a case study design, conducted in July 2025. Data were collected through interviews, observations, and documentation. The results indicate that coaching supervision plays a significant role in enhancing teachers' pedagogical, professional, social, and personal competencies, as well as positively influencing the work motivation of teachers at SD Negeri Bambel Subdistrict, East Aceh Regency. Challenges identified include the limited time of school principals and the lack of initial understanding and knowledge among teachers about coaching. The study recommends further training for school principals and the provision of supporting resources to optimize coaching supervision in improving the quality of education at the State Elementary School in Bambel Sub-district, East Aceh Regency.